2023
DOI: 10.1002/adma.202308429
|View full text |Cite
|
Sign up to set email alerts
|

Space‐Confined Synthesis of Monolayer Graphdiyne in MXene Interlayer

Jiaqiang Li,
Haicheng Cao,
Qingxiao Wang
et al.

Abstract: Graphdiyne (GDY) is an artificial carbon allotrope that is conceptually similar to graphene but composed of sp‐ and sp2‐hybridized carbon atoms. Monolayer GDY (ML‐GDY) is predicted to be an ideal two‐dimensional (2D) semiconductor material with a wide range of applications. However, its synthesis has posed a significant challenge, leading to difficulties in experimentally validating theoretical properties. Here, we report that in‐situ acetylenic homocoupling of hexaethynylbenzene within the sub‐nanometer inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…29,30 Besides, due to the encapsulation of amorphous polypyrrole on the outer layer, the SAED pattern in Fig. 2f only displayed scattered spots, attributed to the {002} and {110} crystallographic planes of Ti 3 C 2 T x , 31,32 proving the crystal character of MXene. Moreover, the corresponding elemental distribution diagram confirmed the appearance of Si, Ti, C, and N elements (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…29,30 Besides, due to the encapsulation of amorphous polypyrrole on the outer layer, the SAED pattern in Fig. 2f only displayed scattered spots, attributed to the {002} and {110} crystallographic planes of Ti 3 C 2 T x , 31,32 proving the crystal character of MXene. Moreover, the corresponding elemental distribution diagram confirmed the appearance of Si, Ti, C, and N elements (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Li et al 74 reported that in situ acetyl cocoupling of HEB in the subnanolayer interlayer space of MXene effectively prevents out-of-plane growth or vertical stacking of the material, resulting in the production of monolayers of GDY (ML-GDY) with in-plane periodicity. Subsequent exfoliation processes successfully prepared freestanding ML-GDY with micrometer-scale lateral dimensions (Figure 9f−h).…”
Section: Explosion Methodmentioning
confidence: 99%
“…(i) I ds – V ds features of ML-GDY measured at 298 K. The top-left inset is a top-view SEM image of the device, and the bottom-right inset is a cross-sectional HAADF-STEM image of the device. Reproduced with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Synthesis Of Gdy Nanomaterialsmentioning
confidence: 99%
“…A reduction in interlayer spacing and ion diffusion can be directly achieved through monolayer treatment [16]. Larger interlayer spacing allows for greater ion intercalation or deintercalation in the electrolyte, while short-distance ion diffusion can enhance ion diffusion kinetics [17][18][19]. Over the past decade, several strategies, including mechanical exfoliation and lithium ion intercalation, have been developed to obtain single-layer or few-layer MXene from bulk sources [20][21][22].…”
Section: Introductionmentioning
confidence: 99%